Coronal Mass Ejection Effect on Envelopes of Hot Jupiters - Zhilkin, A. G.; Bisikalo, D. V.; Kaygorodov, P. V. (Astronomy reports, 2020)
—Currently, hot Jupiters have extended gaseous (ionospheric) envelopes extending far beyond the Roche lobe. The envelopes are loosely bound to the planet and are subject to a strong influence by stellar wind fluctuations. Since hot Jupiters are close to the parent star, the magnetic field of the stellar wind is an important factor which defines the structure of their magnetospheres. For a typical hot Jupiter, the velocity of stellar wind plasma flowing around the atmosphere is close to the Alfvén velocity. Thus, fluctuations of the stellar wind parameters (density, velocity, magnetic field) can affect conditions for the formation of the bow shock around a hot Jupiter, such as transforming the flow from sub-Alfvén to super-Alfvén regime and back. The study results of three-dimensional numerical MHD simulations confirm that, in a hot Jupiter’s envelope located near the Alfvén point of the stellar wind, both the disappearance and appearance of a detached shock can occur under the influence of a coronal mass ejection. The study also shows that this process can affect the observational manifestations of a hot Jupiter, including the radiation flux in the spectrum’s hard region.